Diversidade de rizóbios nativos de solos do semiárido pernambucano isolados de Enterolobium contortisiliquum (Vell.) Morong. - Paiva, Iracema de Azevedo Monte (2023)
Enterolobium contortisiliquum (Vell.) Morong., known as monkfish or monkey, is a legume native to Brazil that occurs from the north to the south of the country. It has a rustic character and adaptability to the edaphoclimatic conditions of the Brazilian semiarid region. Monkfish is a promising species for recovering degraded areas and establishing symbiosis with nitrogen-fixing bacteria. Noduliferous bacteria in legumes are popularly known as rhizobia, in which they are responsible for up to 100% of biological nitrogen fixation. The search for the selection of efficient rhizobia for the production of inoculants appears as an economic, ecological, and sustainable alternative because of the environmental impacts and the high costs of using nitrogen fertilizers. This work aimed to evaluate the genetic diversity of rhizobia isolated from Enterolobium contortisiliquum nodules from soils in the semiarid region of Pernambuco State. Soils were collected in five municipalities of Pernambuco State: Betânia, Parnamirim, Santa Cruz, Santa Maria da Boa Vista, and Serra Talhada. An experiment was set up under nursery conditions to capture the isolates, using monkfish as a trap plant. After 95 days of experimenting, the nodules were collected, and a superficial disinfestation was carried out. The material was spread in streaks to obtain single colonies in Petri dishes with YMA medium. The isolates obtained were genetically characterized by analysis of fragment amplification of the symbiotic genes nifH and nodC using the DuplexPCR, BOX-PCR, ARDRA and partial sequencing of the 16S rRNA gene. A collection of 207 bacteria was obtained from analyzing 127 nodules. Soil from the municipality of Betânia had the highest number of isolates (56), followed by Parnamirim (55), Serra Talhada (43 isolados), Santa Cruz (31) and Santa Maria da Boa Vista (22). In the analysis of genetic variability by BOX-PCR, the monkfish isolates showed different band profiles, demonstrating high genetic diversity. The 32 isolates that were selected for partial sequencing of the 16S rRNA gene were identified in the following genera: Rhizobium (17), Agrobacterium (3), Bradyrhizobium (2), and Paraburkholderia (1). Non-rhizobial isolates belonging to the genera: Pseudomonas (2), Brucella (2), Labrys (2), Pleomorphomonas (1), Bacillus (1), and Siphonobacter (1) were also identified. These results demonstrate that rhizobia isolated from monkfish root nodules from soils in different semiarid regions of Pernambuco State belong to alpha (Rhizobium, Agrobacterium e Bradyrhizobium) and beta-rhizobia (Paraburkholderia). However, there is a predominance of bacteria belonging to the genus Rhizobium, mainly related to the species R. dioscoreae S-93T (99.09 - 100% similarity).